logs(4x-18)-logs(x-6)=1

Simple and best practice solution for logs(4x-18)-logs(x-6)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for logs(4x-18)-logs(x-6)=1 equation:


Simplifying
logs(4x + -18) + -1logs(x + -6) = 1

Reorder the terms:
glos(-18 + 4x) + -1logs(x + -6) = 1
(-18 * glos + 4x * glos) + -1logs(x + -6) = 1
(-18glos + 4glosx) + -1logs(x + -6) = 1

Reorder the terms:
-18glos + 4glosx + -1glos(-6 + x) = 1
-18glos + 4glosx + (-6 * -1glos + x * -1glos) = 1
-18glos + 4glosx + (6glos + -1glosx) = 1

Reorder the terms:
-18glos + 6glos + 4glosx + -1glosx = 1

Combine like terms: -18glos + 6glos = -12glos
-12glos + 4glosx + -1glosx = 1

Combine like terms: 4glosx + -1glosx = 3glosx
-12glos + 3glosx = 1

Solving
-12glos + 3glosx = 1

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Reorder the terms:
-1 + -12glos + 3glosx = 1 + -1

Combine like terms: 1 + -1 = 0
-1 + -12glos + 3glosx = 0

The solution to this equation could not be determined.

See similar equations:

| 3.8=p/3-7.2 | | y/4=5+1 | | 6(x+3)=18 | | (4x-18)-logs(x-6)=1 | | ((x-2x)+2x(y+10xy))=0 | | (-31)(11)= | | 19x+(-4x+3)=2 | | 3*x-6=2*x+8 | | 4x/2+9 | | y+16/12=7/6-y-4/6 | | 0,5x+(-x+3)=19 | | 3x/2+3=2x/3+8 | | y+6/6=y+8/9 | | 48=3k-90 | | M/1=x+n/p | | 9/10x-9=0 | | N=7-3(1) | | 6x+3/9+2=x+2/3+2+x+1/4 | | N=7-2(1) | | 12=x/-3 | | 5/6x=5 | | N=7-2 | | 13=x/-3-4 | | X+1/2+5=x+4/3+6 | | 12/x=4 | | 1+3n=7 | | 2x/3+9+2x=3x/4+32 | | 3+x=90 | | {4}=3 | | 8x^2-66x+81=0 | | 3+6y=9 | | 0+3n=7 |

Equations solver categories